3D Printed Nitrogen‐Doped Thick Carbon Architectures for Supercapacitor: Ink Rheology and Electrochemical Performance. Issue 10 (7th February 2023) - Zhou, Guoqiang; Li, Mei‐Chun; Liu, Chaozheng; Liu, Chuhang; Li, Zhenglin; Mei, Changtong
Abstract: The 3D printing technique offers huge opportunities for customized thick‐electrode designs with high loading densities to enhance the area capacity in a limited space. However, key challenges remain in formulating 3D printable inks with exceptional rheological performance and facilitating electronic/ion transport in thick bulk electrodes. Herein, a hybrid ink consisting of woody‐derived cellulose nanofibers (CNFs), multiwalled carbon nanotubes (MWCNTs), and urea is formulated for the 3D printing nitrogen‐doped thick electrodes, in which CNFs serve as both dispersing and thickening agents for MWCNTs, whereas urea acts as a doping agent. By systematically tailoring the concentration‐dependent rheological performance and 3D printing process of the ink, a variety of gel architectures with high geometric accuracy and superior shape fidelity are successfully printed. The as‐printed gel architecture is then transformed into a nitrogen‐doped carbon block with a hierarchical porous structure and superior electrochemical performance after freeze‐drying and annealing treatments. Furthermore, a quasi‐solid‐state symmetric supercapacitor assembled with two interdigitated carbon blocks obtained by a 3D printing technique combined with a nitrogen‐doping strategy delivers an energy density of 0.10 mWh cm −2 at 0.56 mW cm −2 . This work provides guidance for the formulation of the printable ink used for 3D printing of high‐performance thick carbon electrodes. Abstract : A 3D printable CMU ink consisting of CNFs, MWCNTs, and urea is successfully developed by rational tailoring the concentration‐dependent rheological performance of inks and optimization of the 3D printing parameters. The N‐doped, hierarchically porous, thick carbon architectures can be achieved by 3D printing, freeze‐drying, and annealing approach, which hold the great potential in customized electrochemical energy storage device.